Selangor Real Estate and Housing Board / Nur Shaida Fariza Hamdan - Hamdan, Nur Shaida Fariza (Universiti Teknologi MARA, Sarawak, 2015)
The Selangor Real Estate and Housing Board was established through Enactment Selangor Real Estate and Housing Board that was gazette under the Selangor State Government Gazette, Enactment No. 14/2011 Volume 54 No. 26 dated December 26, 2001. However, Selangor Real Estate and Housing Board began operations on March 1, 2002. The Selangor Real Estate and Housing Board was located at Bangunan Sultan Salahuddin Abdul Aziz Shah, Tingkat 5, Podium Utara, Persiaran Sultan, Seksyen 5, Selangor, 40503 Shah Alam, Malaysia, (http://lphs.selangor.gov.my/)